A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Characterizing on-road particle number emissions from container diesel trucks using interpretable machine learning - Rui-min Hao; Hong-di He; Hong-mei Zhao; Wen-jian Jia; Zhong-ren Peng; Hui Wang (Atmospheric Pollution Research, 2026)

A multi-layer coupling framework for hydrodynamic simulation of underground station flooding - Dong-Mei Zhang; Hai-Yun Li; Wen-Ding Zhou; Si-Rui Chen; Zhong-Kai Huang (Tunnelling and Underground Space Technology, 2026)

A single N-rich covalent organic framework-based sensor for electrochemical sensing of 2,4,6-trichlorophenol - Wei-Long Shan; Qian Lu; Heng-Ye Li; Zhong-Xia Wang; Rui Zhang; Mei-Jie Wei; Fen-Ying Kong; Wei Wang (Food Chemistry, 2025)

Cassiterite U–Pb ages from the Tin Islands, Indonesia, the southern end of the Southeast Asian tin province - Jie-Hua Yang; Rui-Zhong Hu; Mei-Fu Zhou; Bernd Lehmann; Jun-Hong Zhao; Jing-Hua Wu; Liang Liu; Wei Mao; Zheng-Teng Cui; Mega Fatimah Rosana (Mineralium Deposita, 2025)

Constraints of in-situ elemental and B isotopic compositions of tourmaline on the origin of the Nong Sua Sn deposit, Thailand - Jie-Hua Yang; Rui-Zhong Hu; Liang Liu; Wei Mao; Ya-Zhou Fu; Mei-Fu Zhou; Heng Chen; Alongkot Fanka; Ke-Jun Hou (Mineralium Deposita, 2025)

Ontology-driven knowledge graph for decision-making in resilience enhancement of underground structures: Framework and application - Bin-Lin Gan; Dong-Mei Zhang; Zhong-Kai Huang; Fei-Yu Zheng; Rui Zhu; Wei Zhang (Tunnelling and Underground Space Technology, 2025)

Probabilistic analysis of fire casualties in an urban traffic tunnel considering the uncertainty of vehicle queue - Dong-Mei Zhang; Rui Zhu; Zhong-Kai Huang; Lei Yu (Tunnelling and Underground Space Technology, 2025)

Origin of the giant Devonian Daxigou sedimentary siderite deposit, Central China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Rui-Zhong Hu; Zerui Ray Liu; Yanfeng Zhao (Mineralium Deposita, 2025)

Traffic-based resilience assessment on urban road tunnel affected by fire accident - Rui Zhu; Dong-Mei Zhang; Zhong-Kai Huang; Xiao-yang Guo; Bin-lin Gan; Wen-ding Zhou (Tunnelling and Underground Space Technology, 2025)

Identification and bioactivity evaluation of ring-opening and lactone forms of enterolactone from sheep fed flaxseed cake - Cong-Cong Zhuang; Chun-Rui Liu; Hai-Yan Xu; Xin-Yue Yang; Dan-Dan Wu; Zhong Zheng; Li-Wei Wang; Zheng Liu; Chao-Mei Ma (Natural Product Research, 2025)

Insight of oil-soluble Fe-based catalyst for direct liquefaction of Shangwan coal - Zhi Li; Yuxin Wen; Rui Zhang; Mei Zhong; Haiyun Liu; Xin Zheng; Haoquan Hu; Lijun Jin (Fuel, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Decoding the end-Devonian Hangenberg oceanic anoxia event: Insights from ironstones in South China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Ying Cui; Rui-Zhong Hu; Zerui Ray Liu; Xiyao Li (Earth and Planetary Science Letters, 2025)

Post-modification of covalent organic framework functionalized aminated carbon nanotubes with active site (Fe) for the sensitive detection of luteolin - Ze-Qi Wei; Wei-Long Shan; Lei Li; Heng-Ye Li; Rui Zhang; Juan-Juan Gao; Zhong-Xia Wang; Fen-Ying Kong; Mei-Jie Wei; Wei Wang (Food Chemistry, 2025)

Reversible multilevel stimuli-responsiveness and multicolor room temperature phosphorescence to fluorescence transition based on a metal–organic framework system - Hui-Li Sun; Zhong-Hao Wang; Rui-Qi Huang; Zhuo-Di Chen; Mei Pan (Chemical Engineering Journal, 2025)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Constraints of in-situ elemental compositions and U–Pb ages of cassiterite on the origin of the Cretaceous Gejiu and Dulong tin deposits, SW China: Implications for the linkage of tin belts in SE Asia - Zhi Zhang; Jie-Hua Yang; Rui-Zhong Hu; Bin Fu; Qian Hu; Mei-Fu Zhou (Lithos, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Immobilization of pancreatin based on ultrasound-assisted polydopamine functionalized magnetic porous chitosan for the detoxification of ochratoxin A in wine - Saiqun Wang; Tianmin Guo; Xiaoxue Mei; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Chemistry, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Evaluation of CO2 and NOx emissions from container diesel trucks using a portable emissions measurement system - Hong-mei Zhao; Hong-di He; Dan-ni Lu; Dai Zhou; Chun-xia Lu; Xiao-rui Fang; Zhong-ren Peng (Building and Environment, 2024)

The data as a production factor: nonlinear effects of factor efficiency on haze pollution - Mei-Rui Zhong; Jia-Yu Fu; Han Zou (Environment, Development and Sustainability, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

A single-site porphyrin (Cu)-based COF electrocatalyst for the electrochemical detection of gallic acid sensitively - Mei-Jie Wei; Jing Li; Ze-Qi Wei; Sheng-Feng Zhang; Zhong-Xia Wang; Heng-Ye Li; Rui Zhang; Fen-Ying Kong; Wei Wang (Analytica Chimica Acta, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

International Nuclear Medicine Consensus on the Clinical Use of Amyloid Positron Emission Tomography in Alzheimer’s Disease - Mei Tian; Chuantao Zuo; Ali Cahid Civelek; Ignasi Carrio; Yasuyoshi Watanabe; Keon Wook Kang; Koji Murakami; Valentina Garibotto; John O. Prior; Henryk Barthel; Yihui Guan; Jiaying Lu; et al. (Phenomics, 2023)
Alzheimer’s disease (AD) is the main cause of dementia, with its diagnosis and management remaining challenging. Amyloid positron emission tomography (PET) has become increasingly important in medical practice for patients with AD. To integrate and update previous guidelines in the field, a task group of experts of several disciplines from multiple countries was assembled, and they revised and approved the content related to the application of amyloid PET in the medical settings of cognitively impaired individuals, focusing on clinical scenarios, patient preparation, administered activities, as well as image acquisition, processing, interpretation and reporting. In addition, expert opinions, practices, and protocols of prominent research institutions performing research on amyloid PET of dementia are integrated. With the increasing availability of amyloid PET imaging, a complete and standard pipeline for the entire examination process is essential for clinical practice. This international consensus and practice guideline will help to promote proper clinical use of amyloid PET imaging in patients with AD.

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Comparative assessment of nutritional composition, polyphenol profile and antioxidative properties of wild edible ferns from northeastern China - Yun Guo; Sen Shi; Nan Yang; Mei-Xin Tang; Ze-Jia Duan; Xiao-Rui Guo; Zhong-Hua Tang (Food Research International, 2023)

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

A new C 20 -diterpenoid alkaloid from the lateral roots of Aconitum carmichaeli - Jing Yu; Tian-Peng Yin; Jia-Peng Wang; Rui-Feng Mei; Le Cai; Zhong-Tao Ding (Natural Product Research, 2017)

Genomewide identification and expression analysis of the ARF gene family in apple - XIAO-CUI LUO; MEI-HONG SUN; RUI-RUI XU; HUAI-RUI SHU; JIA-WEI WANG; SHI-ZHONG ZHANG (Journal of Genetics, 2014)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Multiple Mesozoic mineralization events in South China—an introduction to the thematic issue - Rui-Zhong Hu; Mei-Fu Zhou (Mineralium Deposita, 2012)

Phylogenetic relationships between Leymus (Poaceae, Triticeae) and related diploid Triticeae species based on isozyme and genome-specific random amplified polymorphic DNA (RAPD) markers - Rui-Wu Yang; Min-Han Zhong; Xue-Mei Zou; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou (Plant Biosystems, 2012)

Synthesis, Characterization, DNA-Binding and Antiproliferative Activity of Nd(III) Complexes With N-(Nitrogen Heterocyclic) Norcantharidin Acylamide Acid - Wen-Zhong Zhu; Qiu-Yue Lin; Mei Lu; Rui-Ding Hu; Xiao-Liang Zheng; Jian-Ping Cheng; Yun-Yun Wang (Journal of Fluorescence, 2009)